Companion to European Heritage Revivals - Egberts, Linde; Bosma, Koos (Springer International Publishing : Imprint: Springer, 2014)
Are you organising an international heritage project? Turning a so-called 'heritage revival' into a meaningful experience for the general public can be a challenge to historians, archaeologists, museum conservators and tourism professionals alike. This Companion to European Heritage Revivals offers inspiration and new ideas to those who want to engage a large, international audience in activities which bring the past to life. It offers a critical examination of the field's basic concepts and discusses a vast array of 'heritage revival tools', including games, historical re-enactments, 3D-visualisations, films, television documentaries, spatial designs and, most importantly, international heritage routes. Through many case studies, this book demonstrates how various aspects of heritage can be effectively presented by linking historical places and landscapes in a single revival to create a multifaceted but coherent whole. Above all, it shows the exceptional success achieved by projects which consistently focus on creating meaningful experiences together with individual users.